THE EFFECTS OF GREEN HOTEL PRACTICES ON HOTEL IMAGE, VISIT INTENTION, AND WORD-OF-MOUTH: FOCUSING ON THE MODERATING ROLES OF CONSUMER ENVIRONMENTAL WORLDVIEWS - Jeon, Sang Mi; Jeong, Wonho; Kim, Daesung (PEOPLE: International Journal of Social Sciences, 2015)
The objective of this study is to empirically examine the effects of hotel green practices on the image of firms, visit intention, and word-of-mouth. In addition, this study examines the moderating effect of an environmental worldview regarding green hotel attributes and image, and visit intention. A self-administrated survey will be conducted to collect data. For data analysis, simple descriptive statistics, factor analysis, and SEM will be utilized to confirm causal relationships among projected constructs. The results of this study will help hoteliers and hotel developers to understand what green hotel attributes are important and necessary to build favorable hotel images, and help researchers to develop future research projects relating to environmental hotel attributes and consumer behaviors.